Heart failure : a practical guide for diagnosis and management - Katz, Stuart D. (New York : Oxford University Press, 2013)
"Clinical practice consensus guidelines for management of heart failure are available from the American Heart Association/American College of Cardiology, Heart Failure Society of America, Canadian Cardiovascular Society, and European Society of Cardiology. The guidelines from these organizations, based on evidence from clinical trials and expert agreement, are largely concordant and provide useful information for practitioners. Yet, the organization of the guidelines may confound efforts by a practitioner to determine which specific intervention, or combination of interventions, are most appropriate for an individual patient. As part of the Oxford American Cardiology Library, Heart Failure utilizes the staging of heart failure proposed by the ACC/AHA guidelines as a framework to develop a systematic approach for diagnosis and treatment across a broad spectrum of clinical presentations. Each chapter addresses a different stage in the progression of heart failure and provides a patient-centered description of the appropriate diagnostic and treatment options for that setting. Each chapter also incorporates discussion of the diagnosis and treatment options for both low ejection fraction heart failure patients and preserved ejection fraction heart failure patients, of which the latter group comprises at least 50% of all heart failure cases in clinical practice. Heart Failure restructures the information in the clinical guidelines to a format that is more accessible and clinically useful to practitioners"--Provided by publisher
12. Hospital Management of Acute Decompensated Heart Failure13. Transitions of Care; Appendix; Index; A; B; C; D; E; F; G; H; I; J; L; M; N; O; P; Q; R; S; T; U; V; W.
Includes bibliographical references and index.
Print version record.
Added to collection customer.56279.3
Keywords: Heart failure -- Diagnosis; Heart failure -- Treatment; Heart Failure -- diagnosis; Heart Failure -- therapy; Insuffisance cardiaque -- Traitement; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Heart failure -- Diagnosis; Heart failure -- Treatment